"Everything That We Can Do": A Content Analysis of the Protective Strategies Used by GLBTQ Parents. Issue 3 (27th May 2018) - Wheeler, Emily E.; Horne, Sharon G.; Maroney, Meredith; Johnson, Teresa
ABSTRACT: Despite increased access to parenting rights through legal marriage and adoption, U.S. gay, lesbian, bisexual, transgender, and queer (GLBTQ) parents continue to experience varying levels of support for their families. This study explored protective strategies, or actions taken to meet one's safety needs when vulnerable, that GLBTQ parents pursue. This study included 454 GLBTQ parents from a national survey. Participants' open-ended responses about protective strategies were extracted from the survey and analyzed using content analysis. Responses were coded into 10 categories capturing strategies GLBTQ parents used to protect their families. While strategies utilizing legal supports were common, the most cited strategies were symbolic strategies, including creating a family name and developing written statements of parent wishes. Exploratory analyses revealed no difference in mean number of strategies used between parents who reported having legal status as a parent through adoption or listing on the birth certificate and those without legal parenting status. These results suggest that GLBTQ parents, regardless of their legal parenting status, take intentional measures to achieve a sense of safety and increase social support. The findings reiterate the importance of both legal and social support of GLBTQ parents.